Design and Development of a Make-Up Service Portal in Kudus Regency Using the Customer Satisfaction Index Method (Journal of Innovation and Technology Polbeng Series on Informatics (INOVTEK Polbeng - Seri Informatika), 2025)
Cosmetology services play an important role in enhancing an individual's self-confidence. In Kudus Regency, many makeup service providers still rely on manual ordering methods, which are prone to recording errors, limited information on service availability, and miscommunication between customers and service providers. This condition hampers operational efficiency and reduces the level of customer satisfaction. This research aims to develop a digital-based make-up service portal to improve service quality and customer satisfaction, which consists of the stages of needs analysis, system design, implementation, testing and maintenance The research method used is qualitative research; data is collected through in-depth interviews with customers, which consists of the stages of needs analysis, system design, implementation, testing, and maintenance. The system developed has main features such as online ordering and service catalogues, as well as CSI-based customer satisfaction evaluations that measure aspects of price, service quality, and user experience. Evaluation using the CSI method shows a customer satisfaction level of 88% with 300 respondents, which indicates that this system is effective in improving user experience and operational efficiency of service providers. In conclusion, the development of this digital-based make-up service portal has succeeded in increasing customer satisfaction and the competitiveness of make-up service providers in Kudus Regency. Further development recommendations are integration with digital payment systems and the use of artificial intelligence technology for more personalized service recommendations.